Analysis of the Eco Centers efficiency through georeferencing irregular disposal areas of construction and demolition wastes - Peixoto Rosado, Lais; Santos Giordano Penteado, Carmenlucia (Sociedade & Natureza, 2018)
Managing the solid waste generated in a city is a major challenge for the municipal government, since it involves high costs and, when not properly managed,can resultin environmental and social impacts. Regarding to construction and demolition wastes (C&DW), municipalities are responsible for the management of C&DW generatedby small generators. In order to attend this demand, the municipalities have started to implement points of delivery of small volumes of C&DW or Eco Centers. However, despite the existence of these points, a considerable amount of debris is daily disposed in inappropriate areas. Thus, this study aims to evaluate the Eco Centers efficiency in the city of Limeira/SP through georeferencing irregular disposal areas of C&DW. It is presented a background of implementation and operation of Eco Centers, highlighting the advantages and disadvantages of this preventive management model. Based on the information obtained, it was concluded that irregular disposal of C&DW are still frequent, even in areas close to Eco Centers, confirming the need of effective monitoring programs and environmental communication and cultural change of the citizens.